Strategic Planning of The Company's Entry into Foreign Markets in The Context of The New Economic Reality (COVID-19) - Erlong Ke; Tatiana Ushkats (Communications of International Proceedings, 2021)
The coronavirus (COVID-19) pandemic has led to a slowdown in the global economy and has become a challenge for all manufacturing sectors: demand has fallen, logistics processes have become more complex, production chains have been disrupted. The pandemic and the subsequent introduction of quarantines in various countries and regions have caused significant changes in energy markets. The changes that have taken place are very significant in the short term and have equally important consequences in the long term for all sectors of the energy complex. The transition to a new level of development of companies in the form of digitalization can help to overcome the crisis in the energy industry and enable companies to develop their business in new conditions.
Keywords: Strategy; Planning; Digitalization; Pandemic; Foreign Markets; Energy; Energy Industry.